Influence of combined pathogenetic treatment on the dynamics of epicardial fat thickness in patients with cad and metabolic syndrome - Kim, Andrey; Shek, Aleksandr; Alieva, Rano (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. To evaluate the influence of combined hypolipidemic therapy (statins in combination with ezetimibe and fenofibrate) and sodium-glucose cotransporter 2 inhibitors on epicardial fat thickness in patients with coronary heart disease and metabolic syndrome.     Materials and methods: The study included 49 patients with coronary heart disease and metabolic syndrome who underwent treatment at the Republican Specialized Scientific and Practical Medical Center of Cardiology. The patients were divided into 2 groups: 1) intensive statin therapy in combination with ezetimibe, 2) with the addition of fenofibrate and SGLT2 inhibitors. All patients underwent biochemical tests and imaging marker assessments, followed by comparison of the dynamics within and between groups.Results. When comparing two groups receiving different types of therapy, both groups demonstrated a significant decrease in lipid parameters: LDL-C p